Evaluating the Effectiveness and Impact of Government Policies on Drug Eradication: A Comparative Analysis of Punitive, Harm Reduction, and Decriminalization Approaches - Harve, Donal Wilson (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2024)
This research examines the effectiveness and impact of various government policies on drug eradication, focusing on punitive approaches, harm reduction strategies, and decriminalization/legalization efforts. The study reveals that traditional punitive measures, which emphasize criminalization and severe penalties, have been largely ineffective in reducing drug use and availability. Instead, these approaches have contributed to mass incarceration, social and racial inequalities, and significant economic and social costs. In contrast, harm reduction strategies, such as needle exchange programs and supervised injection sites, have shown substantial success in improving public health outcomes and proving cost-effective. Additionally, decriminalization and legalization efforts, particularly those involving the regulation of substances like cannabis, offer promising results, including increased tax revenues and reduced enforcement costs. The research highlights the importance of shifting towards evidence-based, public health-oriented approaches and addressing underlying social determinants of health. The findings contribute to a more nuanced understanding of drug policy effectiveness and offer valuable insights for future research and policy development.